Themenopause "penalty" - Gabriella Conti; Rita Ginja; Petra Persson; Barton Willage (Institute for Fiscal Studies (IFS), 2024)
Menopause is a major biological shock to women, marking the end of their reproductive years. Despite its relevance, scant research has studied how menopause impacts social dynamics, labor market outcomes, or health care demand. Using high-quality linked national register administrative data from Norway and Sweden, combined with a stacked difference-in-differences design, we estimate the effect of menopause diagnosis on employment and earnings, reliance on social safety net programs, and demand for medical care. We find that menopause affects a broad swath of women's lives, ranging from a temporary increase in visits to doctors, to a persistent decline in full-time employment and earnings, and an increased receipt of social transfers. The earnings losses amount to 20% relative to the pre-menopause levels. Our results suggest that policies aimed at supporting women who suffer more serious symptoms around the menopausal transition may have wide-ranging benefits.
Keywords: 330